Theory of statistical inference and information - Vajda Igor (Dordrecht Kluwer Academic, 1989)
This book contributes to the literature on mathematical statistics in two ways: one using the results of convex analysis in spaces of measures and secondly the new methods are introduced and studied in light of the general mathematical background includi
Keywords: Statistical inference